2019
DOI: 10.1039/c9nr01075k
|View full text |Cite
|
Sign up to set email alerts
|

Antifolate SERS-active nanovectors: quantitative drug nanostructuring and selective cell targeting for effective theranostics

Abstract: Antifolate plasmonic nanovectors (NVs) are proposed. SERS and cytotoxicity studies on non-cancer and cancer cells reveal the efficient targeting and killing of cancer cells. The selectivity is optimized by coloading folate and antifolate on the NV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Moreover, lysozyme fibrillation has already been characterised by optical and near-field microscopies as well as with conventional spectroscopic techniques 28,29 . AuNPs are currently broadly tested in nanomedicine due to their good biocompatibility and their flexible optical properties which make them well-suited for chemical sensing and drug delivery [30][31][32] In the present contribution, complementary TERS and SERS experiments were performed as sketched in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lysozyme fibrillation has already been characterised by optical and near-field microscopies as well as with conventional spectroscopic techniques 28,29 . AuNPs are currently broadly tested in nanomedicine due to their good biocompatibility and their flexible optical properties which make them well-suited for chemical sensing and drug delivery [30][31][32] In the present contribution, complementary TERS and SERS experiments were performed as sketched in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…They are inert and stable under most environmental conditions and exhibit low toxicity [14]. In addition, they allow for easy manipulation and surface conjugation, by both covalent and noncovalent interactions, with functional agents [16][17][18]. On top of this, AuNPs provide further antibacterial mechanisms, arising from their versatile optical and photothermal properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…The plasmonic coupling of metallic nanostructures under the excitation of incident light has not only drawn substantial interest but also looks promising for applications in optical sensing, solar energy, biomedical therapy, , and especially surface-enhanced Raman spectroscopy (SERS). The vibrational Raman fingerprints of target molecules can be enhanced several orders of magnitude because of the synergistic coupling of localized surface plasmon resonances (LSPR) of nanoparticles (NPs), , surface modified planar substrates, or a combination of both. ,, Previous reports based on deposited NPs or lithographic features , on dry substrates have beautifully demonstrated that the surrounding media, metal species, size, shape, interparticle distance, , and the gap between the substrate and NPs are crucial for the resonance strength, frequency, and the resultant SERS signals. The latter is caused by the local near-field enhancement (“hot spots”) inside or around these nanostructures.…”
mentioning
confidence: 99%